Editorials - Abukari, Abdulai (2020)
The Journal for Researching Education Practice and Theory (JREPT) is once again privileged to present papers based on research from practitioners from a range of practice settings as part of its mission to share practice among practitioners, researchers and other stakeholders in education. This issue presents five papers as follows: